The evolutionary origins of cell type diversification and the role of intrinsically disordered proteins. (1st February 2018) - Niklas, Karl J; Dunker, A Keith; Yruela, Inmaculada
Abstract : We review the evidence that intrinsically disordered proteins played a pivotal role in the evolution of cell type specialization and multicellularity across all major eukaryotic clades. abstract: The evolution of complex multicellular life forms occurred multiple times and was attended by cell type specialization. We review seven lines of evidence indicating that intrinsically disordered/ductile proteins (IDPs) played a significant role in the evolution of multicellularity and cell type specification: (i) most eukaryotic transcription factors (TFs) and multifunctional enzymes contain disproportionately long IDP sequences (≥30 residues in length), whereas highly conserved enzymes are normally IDP region poor; (ii) ~80% of the proteome involved in development are IDPs; (iii) the majority of proteins undergoing alternative splicing (AS) of pre-mRNA contain significant IDP regions; (iv) proteins encoded by DNA regions flanking crossing-over 'hot spots' are significantly enriched in IDP regions; (v) IDP regions are disproportionately subject to combinatorial post-translational modifications (PTMs) as well as AS; (vi) proteins involved in transcription and RNA processing are enriched in IDP regions; and (vii) a strong positive correlation exists between the number of different cell types and the IDP proteome fraction across a broad spectrum of uni- and multicellular algae, plants, and animals. We argue that the multifunctionalities conferred by IDPs and the disproportionate involvement of IDPs with AS and PTMs provided a IDP–AS–PTM 'motif' that significantly contributed to the evolution of multicellularity in all major eukaryotic lineages.